Practical Blazor Debugging : Debugging Blazor WebAssembly Applications with Visual Studio and Blazor Server-Side Features - Himschoot, Peter (Apress, 2020)
This video shows how to improve Blazor's debugging experience by structuring applications to be easily moved between server- and client-side deployments. Practices shown allow the full use of Visual Studio 2019's debugging features even when the target deployment is WebAssembly on the client. You'll learn how to develop and debug using Blazor's server-side support using the extensive debugging support from Visual Studio, then how to move your fully debugged applications into WebAssembly on the client. You'll be able to use the full debugging features of Visual Studio even when your deployment target is client side. What You Will Learn Debug Blazor applications, both server side and WebAssembly Structure Blazor applications and build services for maximum reuse Find and fix bugs faster using advanced breakpoints and watches Use Blazor component libraries to build both server-side and WebAssembly applications Develop and debug JavaScript Interup, again for maximum reuse Gain insight into your code's behavior through detailed logging Who This Video Is For Blazor developers who want to use Visual Studio's debugger to get better insight into their application's behavior. Also developers who want to overcome the weak debugging support for client-side Blazor development. Also programmers who want to build Blazor applications that support both server-side and WebAssembly deployments with maximum reuse.